K-Motion (2018)
K-MOTION, a company that makes a smart vest currently used primarily by golfers and baseball players to analyze their movements, says that in the near future the company's products will understand an athlete's body well enough to make real-time suggestions for ways to have a more productive workout. K-Motion, the maker of K-Coach and K-Player, is the industry leader in wireless, human motion learning for the sports, fitness and medical (physical therapy) industries. The company`s cloud-based products create a complete end-to-end training solution that empowers coaches to get athlete`s and patients better faster. The company combines industry leading sensor accuracy with never before seen software features in a highly reliable, easy to use product that helps top golf coaches, baseball coaches, movement and fitness specialists and physical therapists. K-Motion works with seven of the Top Ten on the Golf Digest Top Teachers List, Major League Baseball and National Hockey League teams, world-renowned fitness coaches and physical therapists as well as Olympic athletes.